Kontribusi Pendidikan Agama Kristen Terhadap Kehidupan Harmonis di Masyarakat Majemuk - Denisman Laia; Ebenezer Gulo; Liena Hulu; Semuel Linggi Topayung (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Indonesia is a countryrich in cultural, ethnic, linguistic, and religious diversity, which requires ongoing efforts to maintain social harmony. However, this diversity also presents unique challenges, particularly concerning potential social conflicts due to differences in values and beliefs. Christian Religious Education (CRE) plays an important role in shaping the character and attitudes of students to enable them to live harmoniously in a pluralistic society. CRE not only focuses on teaching religious doctrines but also imparts universal values, such as love, tolerance, and justice, which can support the creation of a peaceful society. By internalizing these values, students are expected to understand and respect differences and contribute to communal welfare. Nevertheless, implementing CRE in a diverse society also faces various challenges that require synergistic support from various stakeholders. This study aims to deepen the understanding of CRE’s contribution to creating harmonious living in Indonesia’s diverse society and to identify optimal strategies to enhance CRE’s role in educating the younger generation to coexist peacefully.